Clinical Characteristic of Young Indonesian Colorectal Cancer Patients: A Preliminary Study - Nata Pratama Lugito (Medicinus, 2018)
Introduction: Colorectal cancer (CRC) is generally a disease of persons aged above 40 year-old. Controversies still exist regarding clinical characteristics of CRC in young persons. The aim of this study is to know the clinical characteristics of young CRC patients in Siloam General Hospital, Karawaci, Banten.Material And Methods: A total of 14 patients with diagnosis of CRC from December 2013 to January 2014 in Siloam General Hospital, Karawaci, Banten were studied cross – sectionally.  The symptoms and signs, family history of cancer, diabetes, location of mass were collected and evaluated.Results: There were 5 (35.7%) cases of CRC patients aged below 40 year-old (young patients) and 9 (64.3%) above 40 years-old (old patients). The most common symptom was constipation followed by bloody diarrhea i.e. 57.1% and 42.9% consecutively. Constipation occurred in 2 and 6 young and old patients consecutively and in 3 and 3 young and old patients consecutively. In young patients, 2 (14.2%) had a history of cancer in the family compared to none in the old patients. According to the location of tumor in the colon 4 (28.5%) were in ascending colon with 2 and 2 in young and old patients consecutively, 3 (21.7%) were in descending colon with 2 and 1 in young and old patients consecutively, 8 (57.1%) were in rectum with 2 and 6 in young and old patients consecutively. One young patient had diabetes, and one other young patient had positive Clostridium difficile antigen and toxin.Conclusion: Approximately 35.7% cases CRC patient in our hospital was of young patients. Two patients were having family history of cancer. The location of mass was not specific for young CRC patients.Key words: colorectal cancer, young patients